PHENOTYPIC CHARACTERISTICS OF SWAMP BUFFALOES OF MANIPUR* - KHOGEND, R.K.; SINGH, RAJIT; GOGOI, A.K.; AMONGE, T.K.; LASKAR, S.K.; SAIKIA, J. K. (Indian Journal of Animal Production and Management, 2017)
ABSTRACTAn investigation was carried out to study certain phenotypic characteristics of swamptype buffaloes of Manipur in 2009 - 2010. Average body weight, body length, heart girth, height atwithers, pouch girth and length of tail were found to be 223.06 ± 6.70 kg, 98.96 ± 1.16, 142.60± 1.60, 108.85 ± 0.92, 149.29 ± 1.61 and 46.78 ± 0.95 cm respectively. Significant effect wasobserved on all these phenotypic characteristics due to age group and sex while type exertedno significant effect on the above characteristics. All these phenotypic characteristics exhibitedan increasing trend with the advancement of age. Higher values were recorded in males thanthe females on all these phenotypic characteristics.Key words : Swamp buffalo, Manipur, Semi-wild.